The phenomenon of metaphor in the parsing between rhetoricians and grammarians - . Ali Musa Okla. ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The metaphor of the parsing is a phenomenon called changing the parsing of the word because of deletion or addition, and it is divided into two parts: the metaphor for deletion and the metaphor for addition, and these two types do not enter “the well-known metaphor term” in the science of rhetoric, and therefore the opinions of scholars differed on this metaphor, and they differed in determining its type and position. This research tries to provide evidence that the metaphor of the parsing is a phenomenon related to the characteristics of the structures of the Arabic style, and the phenomena that occur to them such as deletion and addition, so it is better to study in the science of meanings or in the science of grammar, It is not related to metaphor. The research included an introduction to concepts and terminology, and four sections, which dealt with this phenomenon among the rhetoricians and grammarians, and a conclusion with the most important findings of the research.